Analisis Faktor yang Mempengaruhi Kebijakan Hutang Emiten Pertanian di Bursa Efek Indonesia - Ramadhany, Reza; Aminah, Mimin; Permanasari, Yusrina (IPB University, 2015)
In financial management perspective, corporate goal is to maximize shareholder or corporate value. The purpose of this study was to analyze the effect of institutional ownership (INST), asset structure (FAR), profitability (ROA), and corporate growth (GROWTH) on debt policy. This study used linear and multiple regression analysis. Significant test results of individual parameters (t statistical test) showed that significant value of INST variable 0.058 < 0.1 (α) and -0.632 (β), FAR 0.097 < 0.1 (α) and 1.019 (β), ROA 0.043 < 0.1 (α) and -1.198 (β), and GROWTH 0.064 < 0.1 (α) and 0.972 (β). The results showed that INST and ROA significantly and negatively affect debt policies, while FAR and GROWTH were significantly and positively affect on debt policies. Whereas, test result of simultaneous (F statistical test) showed that significant value was 0.010 < 0.1 (α) and the value of F calculated was 4.184 > 2.184 F table. These results indicated that institutional ownership, asset structure, profitability, and corporate growth had a significant effect on debt policy simultaneously.Keywords : institutional ownership, structure of assets, profitability, corporate growth